Single-sensor-based dynamic response reconstruction of blades under base excitation. (1st June 2023) - Zhou, Kai; Wang, Yanan; Qiao, Baijie; Fu, Shunguo; Luo, Xianqiang; Chen, Xuefeng
Highlights: A single-sensor-based dynamic response reconstruction method for blades is proposed. Full-field dynamic response reconstruction is conducted on a fan blade. The reconstruction is realized under multi-frequency periodic base excitation. The reconstructed responses are compared with the measured results. The proposed method works whether the blade is in a resonant state or not. Abstract: Blades in the turbo-machinery are inevitably excited by base excitation in addition to unbalanced excitation of the rotor during operation. Accurate measurements of the dynamic response under base excitation are especially critical, which feasibly provides essential guidance on vibration fatigue analysis and remaining life prediction of blades. However, due to some practical factors such as the restriction of the sensor installation position and the inability to directly obtain the external load information, there are still significant challenges in obtaining dynamic response of blades at critical positions under base excitation. In this paper, a novel method is proposed to reconstruct the dynamic response of blades under base excitation, where the measurement of only one sensor is adopted. The method comprises mostly of two steps. The measured signal is first divided into single-frequency response components using empirical mode decomposition with intermittency criteria (EMDIC), and the response components are then classified into two groups depending on whether the frequency is the blade's natural frequency. Then, by combing the time-domain and frequency-domain response transmissibility matrices under base excitation (RTMBE) derived in this paper, the dynamic response of the blade can be reconstructed, whether the blade is in the resonant or non-resonant state. This paper presents numerical simulation and experimental research on a titanium alloy fan blade. The effects of single-and multi-frequency excitation, measurement noise, and measuring point selection on the results of response reconstruction are all investigated. The results demonstrate the feasibility of the response reconstruction method presented in this work for the dynamic response reconstruction of blades under base excitation.